Pelatihan Guru SDN 4 Wagir Lor Ngebel dalam Strategi Pembelajaran Membaca Bagi Anak Kelas Rendah - Della Alfiyanti; Abdah Munfaridatus Sholihah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Reading ability is a fundamental skill that is crucial for lower-grade students in elementary education. Teachers play a acentral role in developing these skills through approppriate learning strategies. This article aims to describe the result of teacher training in implementing effective reading learning strategies for lower-grade students. The training focused on interactive and multisensory approaches, such as phonics-based reading methods, the use of visual media, and story telling techniques. This service uses the ABCD method. Data were collected through observation, interviews, and documents analysis.the result indicate that the training significantly improved teachers understanding of reading strategies and increased the variety of methods used in classroom instruction. Furthermore, students demonstrated greater enthusiasm and comprehension of reading material after teachers implemented the strategies learned in the training. These findings indicate the importance of on going training for teachers in developing reading learning strategies appropriate to the characteristics of lower-grade students.